Evaluasi Optimalisasi Cash Flow Pada Proyek Multiyears Dengan Penyesuaian Perubahan Waktu Pelaksanaan (Studi Kasus Proyek Pembangunan Jalur Kereta Api Lintas Makassar-Pare pare) - Andi Bongawali; Henny Pratiwi Adi; Juny Andry Sulistyo (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
The construction of the Trans-Sulawesi railway line is a railway network built to reach important areas on the island of Sulawesi. In general, the implementation of construction projects is limited by a certain time with limited resources to complete a given job, but due to the unavailability of land when the Work Start Order is issued, it causes a time addendum twice without any cost escalation. The purpose of this research is to get the optimal cash flow that can be obtained by contractors based on changes in implementation time and get the right strategy that can be applied in the future so that no more Addendum changes in implementation time can harm the implementing contractor. Data collection includes primary data by interviewing 25 respondents representing 155 populations consisting of 15 work units, 10 supervisory consultants, 25 implementing contractors and 105 land owners. Secondary data collection was carried out by requesting the necessary data from the implementing contractor. Cash Flow optimization evaluation is carried out by calculating 2 cash flow simulations, namely: Simulation 1 (823 days based on addendum 1), simulation 2 (1063 days / based on addendum 2). Determination of the right strategy to avoid addendum changes in implementation time is done using SWOT Analysis. Calculation of both simulations obtained results: In Simulation 1 (823 days) the acceleration of the implementer